Mechanical properties of concrete produced from waste oil palm shell (OPS) coated with PolyVinyl Alcohol (PVA) as aggregates - Chai, WWS; Teo, DCL; Ng, CK (Engineers Australia, 2013)
Oil palm shell (OPS) is a by-product generated from the palm oil industry. Although OPS can be reused as burning material and raw material for road filling in palm mills, most of these OPS are normally being dumped as waste which causes environmental degradation. Consequently, studies on the use of OPS as concrete aggregate replacement has been gaining increased interest especially in countries where OPS are available in abundance such as in Malaysia. Results from previous studies have shown that OPS concrete can be used in practical applications as structural lightweight concrete. However, the properties of OPS can be further improved to achieve better performance of the resulting concrete. This can be achieved by treating the raw OPS with PolyVinyl Alcohol (PVA). In this investigation, 20% PVA solution was used. A suitable concrete mix proportion containing PVA treated OPS aggregates was first prepared. The resulting concrete properties namely slump, fresh and air-dry density, compressive strength, tensile splitting strength and flexural strength were determined. It was found that PVA treated OPS concrete has significant improvement in its overall concrete strength as compared to raw OPS concrete. There were improvements of 15.22%, 14.86% and 48.27% in its compressive strength, tensile splitting strength and flexural strength respectively. PVA treated OPS concrete can achieve a 28-day compressive strength of up to 33.53 MPa. Laboratory investigations show encouraging results and it can be summarised that 20% PVA solution can be used to improve the OPS concrete properties for the production of structural lightweight concrete.